Compressive Super-Resolution Imaging Based on Scrambled Block Hadamard Ensemble - Yicheng Sun; Xiubao Sui; Guohua Gu; Yuan Liu; Shuangshuang Xu (IEEE Photonics Journal)
Recent advances in the field of compressive sensing indicate that it is possible to robustly reconstruct images from judicious compressive samples. In this paper, we propose a novel model to achieve compressive super-resolution imaging based on an optical realization of scrambled block Hadamard ensemble sensing operation. We further demonstrate that the proposed model can achieve a four-time higher spatial resolution imaging with a small number of measurements in a single-shot acquisition process.